To solve the equation \( 3(-4x-3) = -27 \), we start by simplifying the left side:
-
Distribute the 3: \[ 3 \times -4x + 3 \times -3 = -12x - 9 \] This gives us: \[ -12x - 9 = -27 \]
-
Next, add 9 to both sides to isolate the term with \( x \): \[ -12x - 9 + 9 = -27 + 9 \] This simplifies to: \[ -12x = -18 \]
-
Now, divide both sides by -12 to solve for \( x \): \[ x = \frac{-18}{-12} = \frac{18}{12} = \frac{3}{2} \]
Thus the correct answer for \( x \) is: \[ x = 1.5 \]
However, this value doesn't match with the options provided. Let's check the provided choices:
- \( 0x = -2 \) (not valid - no 'x' term)
- \( x = -3 \)
- \( 0x = 2 \) (not valid - no 'x' term)
- \( 0x = 3 \) (not valid - no 'x' term)
None of the listed options match \( x = 1.5 \). If you intended the choices to match, please check the original equation or choices again.
But if we must pick from the given choices, none of them are valid based on the computation shown.